KEANEKARAGAMAN TUMBUHAN PAKU (PTERIDOPHYTA) DI DAERAH ALIRAN SUNGAI PEPUWATU DESA PRAI PAHA KABUPATEN SUMBA TIMUR SEBAGAI SUMBER BELAJAR BIOLOGI - Patresia Taba Leki; Yohana Makaborang; Yohana Ndjoeroemana (BIOEDUKASI (Jurnal Pendidikan Biologi), 2022)
This study aims to describe the diversity of ferns found in the Pepuwatu River Basin, Prai Paha Village, East Sumba Regency, and to describe the ferns in the Pepuwatu River Basin, Prai Paha Village, East Sumba Regency as a learning resource. Biology in booklet form. This type of research is ecological research with a quantitative descriptive approach. The method used is the eruise method. The results of the study found 450 individuals from 15.  The index of fern diversity in the Pepuwatu River watershed was 1, 948 in the medium category. The product produced in the study is a learning resource in the form of a booklet. Based on the results of the booklet validation test from validator I, which is 100%, validator II is 98.33% and validator III is 96.6%. This means that this booklet is feasible to use in supporting the learning process.Kata Kunci : sumber belajar biologi, keanekaragaman, tumbuhan paku.